Assembling a Justified List of Academic Words in Veterinary Medicine: The Veterinary Medicine Academic Word List (VMAWL) - Ozer, Mustafa; Akbas, Erdem (Pergamon-Elsevier Science Ltd, 2024)
The assembly of corpus-based discipline-specific word lists for pedagogical purposes has recently been on the rise (e.g., Arndt, 2022; Fraser, 2007; O'Flynn, 2019; Yang, 2015). In order to cater to the needs of learners in veterinary medicine (VM) and for field-specific academic literacy, this paper analyses a reiteration of the Veterinary Medicine Corpus (ozer and Akbas, , 2023; hereafter the VMC), assembling a specified list of academic words used in published research articles (RAs) in VM. So far, VM has remained largely unexplored with the exception of Durrant's (2009) limited coverage of VM texts. The analysis was conducted using LancsBox 6.0, prompted to yield a list of PoS-tagged lemmas (Plemmas) sorted by frequency (Coxhead, 2000; Yang, 2015) and dispersion (Arndt, 2022). The most frequent 1,000 lemmas for each content word category were collated into a candidate list. We then manually eliminated proper nouns and GSL (West, 1953) words. The final list, the Veterinary Medicine Academic Word List (VMAWL), contains 835 PoStagged lemmas (P-lemmas), a reiteration of which was produced by adding the types in Bauer and Nation's (1993) taxonomy at the second level to test coverage. The VMAWL was profiled and validated against the four parent categories independently on AntWordProfiler (Anthony, 2022a) with analysis showing the VMAWL comprises 13.75 % of the VMC and diverges greatly from generic word lists like the AWL, NGSL, new-GSL, and AVL. The list can be used to develop teaching materials for EAP or ESP academic writing courses. (c) 2023 Elsevier Ltd. All rights reserved.
Akbas, Erdem/0000-0003-2204-3119; Ozer, Mustafa/0000-0002-7468-2150;
Keywords: English For Veterinary Medicine; Academic English; Academic Word List; Discipline-Specific Academic Vocabulary; Corpus Linguistics